The Nutritional Profile of Indonesian Salmon Van Java Mahseer T. Soro Species - Ekowati Chasanah; Diini Fithriani; Achmad Poernomo; Mohammad Halim Jeinie; Nurul Huda (HACCP Consulting, 2021)
T. soro, in Indonesia called salmon van Java is of high economic value, and due to high demand, its culture has been intensively studied and developed. This study aimed to assess the nutritional value of wild and cultured T. soro. The fish’s proximate compositions, minerals, as well as amino and fatty acid profiles were analyzed. A t-test analysis was used to identify differences between treatments. Results showed that the fat content of wild T. soro was higher than that of cultured fish, but the protein, water, and ash contents between the two groups were not significantly different (p >0.05). T. soro was considered a lean fish with higher concentrations of PUFAs (polyunsaturated fatty acids) than MUFAs (monounsaturated fatty acids). The amino acid profile was dominated by lysine, phenylalanine, and allo-isoleucine. Both groups of fish were a good source of macro- (Na, K, Ca) and microminerals (Zn, Fe), except for selenium (Se). The two groups were not significantly different (p >0.05) in ω3, ω6, and PUFAs, indicating that culturing T. soro in proper ways could substitute for wild T. soro.